Physiological levels of adrenaline fail to stop pancreatic beta cell activity at unphysiologically high glucose levels - Sluga, Nastja; Križančić Bombek, Lidija; Kerčmar, Jasmina; Sarikas, Srdjan; Postić, Sandra; Pfabe, Johannes; Skelin Klemen, Maša; Korošak, Dean; Stožer, Andraž; Slak Rupnik, Marjan (Frontiers in Endocrinology, 2022)
Adrenaline inhibits insulin secretion from pancreatic beta cells to allow an organism to cover immediate energy needs by unlocking internal nutrient reserves. The stimulation of α2-adrenergic receptors on the plasma membrane of beta cells reduces their excitability and insulin secretion mostly through diminished cAMP production and downstream desensitization of late step(s) of exocytotic machinery to cytosolic Ca2+ concentration ([Ca2+]c). In most studies unphysiologically high adrenaline concentrations have been used to evaluate the role of adrenergic stimulation in pancreatic endocrine cells. Here we report the effect of physiological adrenaline levels on [Ca2+]c dynamics in beta cell collectives in mice pancreatic tissue slice preparation. We used confocal microscopy with a high spatial and temporal resolution to evaluate glucose-stimulated [Ca2+]c events and their sensitivity to adrenaline. We investigated glucose concentrations from 8-16 mM to assess the concentration of adrenaline that completely abolishes [Ca2+]c events. We show that 8 mM glucose stimulation of beta cell collectives is readily inhibited by the concentration of adrenaline available under physiological conditions, and that sequent stimulation with 12 mM glucose or forskolin in high nM range overrides this inhibition. Accordingly, 12 mM glucose stimulation required at least an order of magnitude higher adrenaline concentration above the physiological level to inhibit the activity. To conclude, higher glucose concentrations stimulate beta cell activity in a non-linear manner and beyond levels that could be inhibited with physiologically available plasma adrenaline concentration.